VIDEO ANALYSIS OF APPARATUS DIFFICULTY AT THE 2019 WORLD CHAMPIONSHIPS BAKU - GAVRILUȚ G.; MORARU C.E; TOMOZEI R.A (Editura Universitatii Transilvania din Brasov, 2020)
The purpose of this paper was to analyse the apparatus difficulty at the World Championships and observe what apparatus gymnasts manage the most valuable handling, but also the differences between the score of the eight finalists for each object and the representatives of Romania, to see how much they have to recover to qualify for this year's Olympics. For this paper we analysed a number of 40 video executions, eight finalists for each object and eight executions of the two representatives of Romania. We conclude that the Romanian gymnasts are far from the average of the finals, the first representative exceeding the minimum value in the finals on two apparatus, and the second on a single object. The highest value of 9.3 points was observed at clubs, the lowest in the ribbon of 4.3 points, the smallest average is also in the ribbon of 5.1 points, and the highest in the hoop of 8.28 points